UJI AKTIVITAS ANTIMIKROBA BAKTERI ENDOFIT PSEUDOMONAS BERFLUORESEN TERHADAP Escherichia coli, Staphylococcus aureus DAN Candida - Fauzi Eka Nuraini; Dwi Hilda Putri; Linda Advinda; Irdawati; Dezi Handayani; Laila Mardhiyah Nazri; Tesya Wulandari; Liza Febrianti (Universitas Cokroaminoto Palopo, 2026)
Antimicrobial resistance is increasing every year. New and better antimicrobial sources are needed. One source of antimicrobials that can be explored is from endophytic bacteria. This study aims to test the ability of fluorescent Pseudomonas endophytic bacteria from the roots of plantain lemongrass in producing antimicrobial compounds. The type of research is descriptive. The antimicrobial activity of fluorescent Pseudomonas isolates was tested using the point inoculation method using test microbes E. coli, S. aureus and C. albicans. The clear zone was observed after 24 hours. The results showed that fluorescent Pseudomonas isolates were able to inhibit E. coli with a diameter of 3.9 mm found in isolate 51. S. aureus bacteria had an inhibition zone of 9.4 mm in isolate 89. Interesting results were shown by isolate 51 in inhibiting C. albicans with an inhibition zone diameter of 29.9 mm. These differences in response are thought to be related to variations in cell wall structure and the presence of an outer membrane in Gram-negative bacteria, which inhibits the penetration of active compounds. Overall, fluorescent Pseudomonas endophytic bacteria from the roots of the plantain have the potential to be developed as a source of new antifungal candidates against C. albicans, while their antibacterial activity still needs to be optimized through compound purification and further testing.